Nitrogen Disturbance Awakening the Intrinsic Activity of Nickel Phosphide for Boosted Hydrogen Evolution Reaction. Issue 16 (4th August 2022) - Yang, Caixia; Wang, Zhiqiang; Li, Zhendong; Pan, Yichen; Jiang, Linwei; Li, Caicai; Wang, Chao; Sun, Qingfeng
Abstract: Invited for this month′s cover is the group of Qingfeng Sun at the Zhejiang A&F University. The image shows that the N‐doped Ni2 P exhibits excellent electrocatalytic activity for hydrogen evolution reaction (HER). The Research Article itself is available at 10.1002/cssc.202200072 . Abstract : "This work provides an atomic‐level insight into the catalyst design…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202200072 . View the Front Cover here: 10.1002/cssc.202201347 .